Trends and opportunities in renewable energy investment in Saudi Arabia: Insights for achieving vision 2030 and enhancing environmental sustainability - Mahmoud Mohamed Selim; Nasser Alshareef (Alexandria Engineering Journal)
Renewable energy has emerged as a critical alternative to traditional energy sources due to growing environmental concerns and the need for sustainable energy development. Saudi Arabia, driven by its Vision 2030, has strongly committed to shifting from fossil fuels to renewable energy sources such as solar, wind, and hydrogen. Despite significant progress, existing investment methods often focus narrowly on financial returns and do not adequately address the risks and uncertainties associated with renewable energy projects, such as policy changes, technological challenges, and fluctuating energy prices. This paper aims to highlight and compare the trends in renewable energy investments and incorporate a risk analysis matrix to address the economic, environmental, and social aspects of Saudi Arabia’s environment. The details used in the study are obtained from Kaggle, while the adopted analysis technique involves multi-criteria decision-making (MCDM). It provides a fresh qualitative approach that allows an all-sided assessment of the investment prospects by focusing on appropriate weight for different factors. The analysis results show that using the proposed framework can help effectively prioritize investment opportunities identifying major trends and risks in developing renewable energy sources in Saudi Arabia. Current investment trends have been reviewed systematically; experts have been interviewed; MCDM techniques have been employed, as the methodology effectiveness improves the comprehension of investment tendencies and contributes to strategic management in the renewable energy market stakeholder’s activity. The MCDM analysis results show that the solar energy system has the highest investment index in the Saudi Arabian cities; the first place belongs to Abha with an investment index of 0.93, the second place belongs to Jeddah with an investment index of 0.85, and the third place belongs to Dammam with an investment index of 0.75. From these outcomes, we can easily conclude that Abha is the best place to place a solar energy project, probably because of environmental and legal factors. The analysis underscores geographic factors in deploying renewable energy, directing investors and policymakers to cities with favourable solar power generation about sustainability and economic objectives. The results are expected to enhance investment awareness among local and international stakeholders, support the strategic goals of Vision 2030, and contribute to a more sustainable and diversified energy future for Saudi Arabia. This study provides a strategic framework for optimizing renewable energy investments, promoting sustainable development, and achieving long-term economic growth. Data Availability: Data sharing is not applicable to this article as no data sets were generated during the current study.